ON EXISTENCE AND CONSTRUCTION OF A GENERAL POLYNOMIAL SOLUTION OF A CLASS OF SECOND ORDER DIFFERENTIAL EQUATIONS' SYSTEMS - Piperevski, Boro (Matematichki Bilten, 2001)
Theorem. Havіng \(ABCD(AD-BC) e 0\) the systеm (1) has a polynomial solution, iff \(n,m\in N\) exist, such that (9) for something \(p\in\{0,1,2,…,m-2\}\).In this case the polynomial solution of the systеm (1) will be given by the formula (10).